Membedah Pesan di Film Taare Zameen Par: Kritik terhadap Penerapan Pendekatan Perilaku dalam Proses Pembelajaran - adita widya pangestika (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2020)
Film is an effective media for social critics. Through the audio visual elements film can display various portraits of social phenomena that exist in the midle of society. This research aims to explore the various signs in the film scenes which are representations of social critics, especially in the field of education. The method used in this study is semiotic developed by John Fiske. The scenes which are considered to contain social critics is elaborated on 9 television codes. After that the sign will be analyzed in three levels, the level of reality, representation, and ideology. This study found that the “Taare Zameen Par” film contained critics of the behavioristic approach in the education system. Efforts to criticize the behavioristic approach are carried out by generating a humanistic approach as a comparison. The main figure who has a dyslexic problem barely can read when educated using the behavioristic approach. He also got the label as a naughty student. The main figure was experiencing significant development when educated using a humanistic approach. In this way film makers try to assert that the behavioristic approach has many weaknesses and is not suitable to be applied in the formal education system.